2017
DOI: 10.3389/fmicb.2017.01483
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Physiologic, and Symbiotic Characterization of Serratia marcescens Strains Isolated from the Mosquito Anopheles stephensi

Abstract: Strains of Serratia marcescens, originally isolated from the gut lumen of adult female Anopheles stephensi mosquitoes, established persistent infection at high rates in adult A. stephensi whether fed to larvae or in the sugar meal to adults. By contrast, the congener S. fonticola originating from Aedes triseriatus had lower infection in A. stephensi, suggesting co-adaptation of Serratia strains in different species of host mosquitoes. Coinfection at high infection rate in adult A. stephensi resulted after feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 87 publications
0
42
0
1
Order By: Relevance
“…Hemolysin production in F. spartansii T16 T was examined by inoculating bacteria on Remel Blood Agar (Thermo Scientific, KS). Hemolytic activity was evaluated following incubation at 28°C for 48 h. The controls for α- and β-hemolysin producers were Elizabethkingia meningoseptica ATCC 13253 and Staphylococcus aureus MSU001, respectively (Chen et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hemolysin production in F. spartansii T16 T was examined by inoculating bacteria on Remel Blood Agar (Thermo Scientific, KS). Hemolytic activity was evaluated following incubation at 28°C for 48 h. The controls for α- and β-hemolysin producers were Elizabethkingia meningoseptica ATCC 13253 and Staphylococcus aureus MSU001, respectively (Chen et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…(Falvibacteriace), Pseudomonas (Pseudomonadales), and Serratia (Enterobacteriace). Previous several studies have also reported a similar pattern of gut microbe enrichment (Tchioffo, Boissiere et al 2015;Muturi, Dunlap et al 2019), but nature of gutmicrobe interactions, especially microbial proteins facilitating blood meal digestion, remains poorly known (Chen, Blom et al 2017). Available draft genome sequence of cultured bacterial species predicts several metabolic pathways, but no functional relation has been established (Kukutla, Lindberg et al 2013;Pei, Hill-Clemons et al 2015).…”
Section: Fig 8 Relative Quantification Of Gut Immune Transcripts Inmentioning
confidence: 99%
“…T2SS was observed only in RPA1, which could explain its higher trypanolytic activity compared to that of RPH1. This secretion system was also detected in S. marcescens strains Ano1 and Ano2, from A. stephensi (Chen et al, 2017), although the mechanism that could interfere with the Plasmodium development in the mosquito midgut has not been described yet.…”
Section: Discussionmentioning
confidence: 99%